Rebranding God: The Jewish Revival Movement between Homeland and Diaspora - Werczberger, Rachel (Religions, 2024)
Against the gloomy forecast of “The Vanishing Diaspora”, the end of the second millennium saw the global emergence of a dazzling array of Jewish cultural initiatives, institutional modalities, and individual practices. These “Jewish Revival” and “Jewish Renewal” projects are led by Jewish NGOs and philanthropic organizations, the Orthodox Teshuva (return to the fold) movement and its well-known emissary Chabad-Lubavitch Hasidism, and alternative cultural initiatives that promote what can be termed “lifestyle Judaism”. This range between institutionalized revival movements and ephemeral event-driven projects circumscribes a diverse space of creative agency. Indeed, the trope of a “Jewish Renaissance” has become both a descriptive category of an increasingly popular and scholarly discourse across the globe, and a prescriptive model for social action. This article explores the global transformations of contemporary Jewishness, which give renewed meaning to identity, tradition, and politics in our post-secular world in two different sociopolitical contexts. Drawing on long-term ethnographic research, we interrogate the relations between “diaspora” and “homeland” by analyzing two case studies: the Jewish revival movement in Budapest, Hungary, and the Jewish renewal initiatives in Israel. While the first instantiates a diasporic movement anchored in a post-denominational and post-secular attempt to reclaim Jewish tradition for a new generation of Jew-llennials (Millennial Jews), the second group operates against the Orthodox hegemony of the institutional Rabbinate by revisiting religious ritual and textual study. By proposing new cultural repertoires, these movements highlight the dialectic exchange between center and periphery. The ethnography of religious revival decenters the Israeli Orthodoxy as “the homeland” and positions the diaspora at the core of a network of cultural creativity and renewal, while remaining in constant dialog with Israel and other diasporic communities.